Efficacy of endometrial cytology and ultrasonography for diagnosis of subclinical endometritis in postpartum Murrah buffaloes - BAJAJ, N K; SWAMY, M; AGRAWAL, S; JAIN, S K; HONPARKHE, M; SHRIVASTAVA, O P (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to investigate the efficacy of trans-rectal ultrasonography and endometrial cytology to diagnose subclinical endometritis in postpartum Murrah buffaloes. Forty two buffaloes (6 normal, 6 clinical endometritic and 30 subclinical endometritic) were selected from college livestock farm and organised farms of Jabalpur. Trans-rectal ultrasonography, endometrial cytology and microbial assay were performed. Efficacy of trans-rectal ultrasonography and endometrial cytology for diagnosis of subclinical endometritis along with microbial assay was recorded as 69.23 and 87.17%, respectively. It is concluded that endometrial cytology iseffective diagnostic technique for diagnosis of subclinical endometritis. Subclinical endometritis cases diagnosed as negative or doubtful by ultrasonography could be confirmed by endometrial cytology.